Unpacking the indirect effects and consequences of environmental regulation - Tan, Kim Hua; Chung, Leanne; Shi, Lei; Chiu, Anthony (Elsevier, 2017)
Environmental regulation and its corresponding measures and control is an important issue but have not been fully investigated. Literature on the unintended consequences of regulation control and measures appears to be sparse. Through a series of exploratory case studies in China, this paper examines the various unintended impacts of ecological civilisation (EC) regulation on firms’ operations and their related consequences to performance. Findings showed that there were interrelated themes that underpin the indirect and unintended effects of regulatory control and performance management. This exploratory study can contribute to both theory building and provide important EC policy implications by: (a) enriching the conceptual understanding of the unintended consequences of environmental regulation on firms’ behaviours and outcomes, (b) providing policy maker important insights and practical advices for regulating environmental performance.